2016
DOI: 10.3389/fphys.2016.00386
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, Inflammation, and Exercise Training: Relative Contribution of iNOS and eNOS in the Modulation of Vascular Function in the Mouse Aorta

Abstract: Background: The understanding of obsesity-related vascular dysfunction remains controversial mainly because of the diseases associated with vascular injury. Exercise training is known to prevent vascular dysfunction. Using an obesity model without comorbidities, we aimed at investigating the underlying mechanism of vascular dysfunction and how exercise interferes with this process.Methods: High-sugar diet was used to induce obesity in mice. Exercise training was performed 5 days/week. Body weight, energy intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 54 publications
3
28
0
6
Order By: Relevance
“…Previous studies have shown the ability of exercise training in reducing circulatory TNF‐α, IL‐6 and IL‐1β levels, in both laboratory animals and humans . In addition, exercise training was effective in reducing inflammatory markers iNOS, TNFR, and phosphorylated IkB‐α in aorta of obese mice . Here, we demonstrated for the first time that the exercise training reduced the iNOS protein expression in PVAT, associated with normalization of anti‐contractile effect of PVAT in the TR‐HF group.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Previous studies have shown the ability of exercise training in reducing circulatory TNF‐α, IL‐6 and IL‐1β levels, in both laboratory animals and humans . In addition, exercise training was effective in reducing inflammatory markers iNOS, TNFR, and phosphorylated IkB‐α in aorta of obese mice . Here, we demonstrated for the first time that the exercise training reduced the iNOS protein expression in PVAT, associated with normalization of anti‐contractile effect of PVAT in the TR‐HF group.…”
Section: Discussionsupporting
confidence: 56%
“…Differently from constitutive NOS (nNOS and eNOS), iNOS is able to produce a huge amount of NO . Interestingly, mice fed a high‐sugar diet for 8 weeks also exhibited elevated iNOS expression in aorta and reduced contractile response to PHE, which was associated with higher NO levels in the vascular tissue . The aortic vasoconstrictor response was normalized by knocking down iNOS, suggesting an important role for iNOS in the vascular changes in response to the early phase of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…L-NIL is considered to be a relative selective iNOS inhibitor, presenting IC50 values of 5.9, 138, and 35  μ M for inhibition of recombinant human iNOS, eNOS, and nNOS isoforms, respectively [39]. Our results suggest that, in thoracic aorta of C57BL/6, L-NIL may inhibit other NOS isoforms in a lower concentration, despite the fact that other studies have found an in situ selective iNOS inhibition in this artery [38, 40]. However, a role of iNOS could be excluded in the reduction of noradrenaline-contraction of thoracic aorta in obese mice because the gene expression of iNOS was similar in control and obese mice.…”
Section: Discussionmentioning
confidence: 62%
“…Silva et al. () reported that treadmill exercise training reversed downregulation of eNOS protein expression in the aorta of high‐sugary diet‐induced obese mice. Together these results suggest that voluntary running can restore NO signaling in the coronary microcirculation of diet‐induced obese mice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ito et al (2015) found that running exercise improved a reduced formation of nitrate/nitrite metabolites in renal cortex and outer medullar of diabetic Zucker rats. Silva et al (2016) reported that treadmill exercise training reversed downregulation of eNOS protein expression in the aorta of high-sugary diet-induced obese mice. Together these results suggest that voluntary running can restore NO signaling in the coronary microcirculation of diet-induced obese mice.…”
Section: Possible Underlying Mechanisms By Which Chronic Voluntary Rumentioning
confidence: 99%